Efektivitas Pengaturan Hukum Pajak E-Commerce Terhadap Peningkatan Penerimaan Pajak Di Indonesia - Davela Navisa Risandhi; I Gusti Ketut Ayu Rachmi Handayani; Fatma Ulfatun Najicha (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to understand the effectiveness of the current tax law regulations regarding e-commerce in Indonesia on state tax revenue. Additionally, it discusses the potential of e-commerce taxation, inhibiting factors, and efforts made by the Directorate General of Taxes to increase tax revenue in Indonesia. This study is an empirical legal research with a qualitative approach. Types and sources of data include primary and secondary data. Data collection techniques used were interviews with representatives from the Direktorat Jendral Pajak, followed by qualitative data analysis techniques. The research findings indicate that the current regulations do not yet cover the taxation of e-commerce itself. The imprecision of regulations leads to the existence of untapped tax potentials if e-commerce taxation is further regulated. Moreover, there are still many taxable entrepreneurs (PKP) who are not compliant in tax payments and reporting. The constantly changing regulations contribute to legal uncertainty in society. Inadequate supervision is also one of the inhibiting factors in realizing the potential increase in tax revenue from e-commerce transactions in Indonesia.